The Role of Total Quality Management in Developing the Concept of Social Responsibility to Protect Public Interest in Associations of Liberal Professions - Cristina Raluca Gh. Popescu (Amfiteatru Economic)
The paper highlights the part of the results of a questionnaire-based research, carried out at the level of associations of liberal professions members of the Liberal Professions Union of Romania (LPUR). It was rated the implementation of the principles of Total Quality Management (TQM) among the 14 member associations of professions and were identified LPUR most important success factors of TQM that can help increase the social responsibility to the public interest associations of members of liberal professions. The research was conducted from April 18 to May 31, 2017 at the headquarters of the professional associations shall LPUR at a representative sample of 100 employees from 130 thereof. They identified 58 strengths confirming a high level of implementation of TQM principles and 28 issues that require improvement. It was identified good results about „activities and general working conditions” and „Quality Control”. At the same time were discovered gaps on the „flexibility of the organization” and in „Identifying and capitalizing expectations in meetings with members”. On the one hand, based on the results analysed, it was determined that „Exigency examinations access to employment” and “Using professional standards” are the factors with the greatest impact on increasing social responsibility and the public interest and, on the other hand “the openness of associations - free competition” has the lowest impact.